Pre-education reflections of online and face-to-face clinical experiences - Carolyn Casale; C. Adrainne Thomas; Ahlam Alma Bazzi (Emerald Publishing, 2024)
Purpose - This research study provides insight into students' perceptions of teaching through virtual and face-to-face clinicals in an introductory education course in a pre-education program at a minority-serving institution. Design/methodology/approach - This study took place at an urban-suburban-centered community college in the Midwestern United States and was reviewed by the higher education institutional review board (IRB). Data were collected from pre-education majors enrolled in a four-hour Introduction to Education with field experiences. Findings - The findings indicated that both virtual and face-to-face clinicals were beneficial to the development of pre-service teachers, particularly in an early introduction to education course. Research limitations/implications - The finding that virtual clinicals are significant to teacher growth is significant to teacher recruitment and preparation. Practical implications - The flexibility of a virtual clinical provides greater opportunities for low-income and marginalized populations with limited means and access. Social implications - This finding can lead to strategies to diversify teacher candidates. Originality/value - This study sought to answer the following question: how do pre-education students reflect to understand the roles and responsibilities of teaching through virtual options vs face-to-face clinicals? The interest of this research is to expand pathways into the teaching profession to nontraditional, ethnically and culturally marginalized groups and historically underrepresented groups.